An Examination of the Effect of Consumer Personal Traits on Show Rooming Behavior: The Effect of Product Type. Issue 1 (2nd January 2019) - Kim, Bumsoo; Park, Min Jae
Abstract: The rapid growth of online commerce and spread of mobile devices have created various trends in product-purchasing behaviors of consumers. Especially in online-to-offline commerce, "showrooming" has increased. This involves searching for products offline but purchasing them online. Among theories of consumer buying behavior based on traditional consumer characteristics, this study empirically analyzes whether there are group-specific differences in showrooming. The results show that innovative consumption tendencies are significantly related to push, pull, and mooring factors. The findings also elucidate the role of showrooming buying behavior in these relationships. In terms of push and mooring factors, these relationships are strengthened by showrooming purchase experience. This study divides products into electronic products and apparel and analyzes the effects on purchase experience using a moderator.